Evaluasi Kebijakan Dinas Pendidikan Terkait Peningkatan Kapasitas Guru di Kabupaten Maluku Tenggara - Djems Raymon Moriolkosu; I. H. Wenno; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2024)
The evaluation of the policies of the Education Department plays a very important role in carrying out the function of realizing the objectives of each Strategy Plan in the form of evaluating each indicator of the objectives of the strategy and indicators of the activities to be achieved in order to improve the capacity and performance of teachers because the Education Department is the institution assigned the task of managing the education of enlightening the human being or in other words the teacher's kitchen. Evaluations are important because to measure the extent to which planning and execution are directly proportional because often planning is only as a document while the implementation is different but in reporting and accountability are reported as planned. This study aims to evaluate whether there are any policies of the Department of Education that are in favor of improving the capacity and performance of teachers. The research method used in this research is a qualitative method with a descriptive type of research document study and interview. This research was conducted at the Southeast Maluku Regency Education Office in 2024. The data collection techniques used were interviews,observation and documentation with questionaire instruments. Next,check the observation data again with the interview results, compare the interview results with the documents. The research results show that from the context aspect, strategic planning documents are prepared base on stages according to planning and policies regarding teacher capacity contained in the main performance indicators, input aspect, evaluation of program planning are clearly depicted but are not supported by standard operating procedures,process aspects, implementation of equalization begins with the initial processes start from preparation,implementation, product aspect, learning results are desplayed but there are No. documents for quarterly, mid-semester or end semester learning results.